Muleteers, troperos and llamaros in Huancavelica - Valderrama Fernández, Ricardo (1983)
Huancavelica owes its foundation to the discovery and exploitation of its quicksilver mines by the Spanish. Being constituted from the beginning and throughout the colonial period in a miners' camp. Located at 3,680 meters above sea level, it must have been supplied with food and other merchandise from the nearby valleys and from the cities of Lima and Huamanga, on which it was dependent. The hauling of these products, as well as the transportation of the mineral, was carried out by the muleteers, an activity that grows parallel to the city and the mining exploitation. The following pages deal with herding in the first half of this century.